Visio-urbanities: "Nossa Vila É" as Public Art within Urban Visual Culture - Pimenta, Bruno Bissoli (Revista do Colóquio, 2026)
This article aims to articulate the visual culture processes present in public art through a systemic understanding of the mural *Nossa Vila É* (Vitória, ES), drawing upon concepts of creative culture (Bosi), the image as a cultural construct (Monteiro), and artistic practices in the public sphere (Furtado). The work emerges as a cultural artifact, reflecting the diversities and tensions between institutionalization and temporality. The study concludes that this practice builds relational bridges, fostering sociocultural and territorial narratives.